LC-MS/MS-based metabolomics and sensory evaluation characterize metabolites and texture of normal and spoiled dry-cured hams. (1st March 2022) - Liao, Renyong; Xia, Qiang; Zhou, Changyu; Geng, Fang; Wang, Ying; Sun, Yangying; He, Jun; Pan, Daodong; Cao, Jinxuan
Highlights: The metabolites and metabolite pathway were evaluated in spoiled dry-cured ham. Amino acid derivatives and oligopeptides were the key components to distinguish spoiled and normal hams. N -acetyl-Met, Ile-Pro, and Ile-Lys-Thr-Lys were responsible for the low scores of overall acceptance in spoiled ham. Purine metabolism, pyrimidine metabolism and protein degradation were the main metabolic pathways in spoiled ham. Abstract: The spoiled dry-cured ham commonly shows unpleasant taste and odour. To deepen the understanding in the formation mechanism of unpleasant taste in spoiled ham, sensory attributes, texture parameters, protein degradation, metabolites were investigated between normal and spoiled hams; the relationship between the sensory quality and metabolites of dry-cured ham was further evaluated by partial least square discriminant analysis (PLS-DA). The scores of richness and overall acceptance were significantly lower in spoiled ham, and more than 12.5-fold values in adhesiveness were found in spoiled ham than normal ham. Myofibrillar proteins including actin, troponin-T and myosin light chain showed excessive degradation in spoiled ham. Forty-two kinds of metabolites mainly derived from protein degradation were identified by LC-MS/MS, and amino acid derivatives and oligopeptides were the key components to distinguish spoiled and normal hams demonstrated by PLS-DA. Purine metabolism, pyrimidine metabolism and protein degradation were the main metabolism pathways in spoiled ham.